Counter-regulation of regulatory T cells by autoreactive CD8+ T cells in rheumatoid arthritis. (May 2019) - Cammarata, Ilenia; Martire, Carmela; Citro, Alessandra; Raimondo, Domenico; Fruci, Doriana; Melaiu, Ombretta; D'Oria, Valentina; Carone, Chiara; Peruzzi, Giovanna; Cerboni, Cristina; Santoni, Angela; Sidney, John; et al.
Abstract: The mechanisms whereby autoreactive T cells escape peripheral tolerance establishing thus autoimmune diseases in humans remain an unresolved question. Here, we demonstrate that autoreactive polyfunctional CD8 + T cells recognizing self-antigens (i.e., vimentin, actin cytoplasmic 1, or non-muscle myosin heavy chain 9 epitopes) with high avidity, counter-regulate Tregs by killing them, in a consistent percentage of rheumatoid arthritis (RA) patients. Indeed, these CD8 + T cells express a phenotype and gene profile of effector (eff) cells and, upon antigen-specific activation, kill Tregs indirectly in an NKG2D-dependent bystander fashion in vitro . This data provides a mechanistic basis for the finding showing that AE-specific (CD107a + ) CD8 + T killer cells correlate, directly with the disease activity score, and inversely with the percentage of activated Tregs, in both steady state and follow-up studies in vivo . In addition, multiplex immunofluorescence imaging analyses of inflamed synovial tissues in vivo show that a remarkable number of CD8 + T cells express granzyme-B and selectively contact FOXP3 + Tregs, some of which are in an apoptotic state, validating hence the possibility that CD8 + Teff cells can counteract neighboring Tregs within inflamed tissues, by killing them. Alternatively, the disease activity score of a different subset of patients is correlated with the expansion of a peculiar subpopulation of autoreactive low avidity, partially-activated (pa)CD8 + T cells that, despite they conserve the conventional naïve (N) phenotype, produce high levels of tumor necrosis factor (TNF)-α and exhibit a gene expression signature of a progressive activation state. Tregs directly correlate with the expansion of this autoreactive (low avidity) paCD8 + TN cell subset in vivo, and efficiently control their differentiation rather their proliferation in vitro . Interestingly, autoreactive high avidity CD8 + Teff cells or low avidity paCD8 + TN cells are significantly expanded in RA patients who would become non-responders or patients who would become responders to TNF-α inhibitor therapy, respectively. These data provide evidence of a previously undescribed role of such mechanisms in the progression and therapy of RA. Highlights: Autoreactive CD8 + TN or eff cells differently affect Tregs to their vantage in RA. Autoreactive low avidity CD8 + TN cells producing TNF-α are sustained by Tregs. Autoreactive high avidity CD8 + Teff cells resist Tregs by killing them. These distinctive mechanisms condition the response to anti-TNF therapy. They could contribute for designing innovative therapeutic strategies.